The mechanism of action of iminosugars as antiretrovirals - Spiro, S; Simon Spiro (2014)
Iminosugars are a class of molecules that resemble sugars but for the substitution of a nitrogen for the oxygen in the hemiacetal ring. Several iminosugars are inhibitors of cellular glycosidase enzymes in the N-linked glycan processing pathway. Iminosugars inhibiting endoplasmic reticulum (ER) α-glucosidases are known to be antiviral against a broad range of enveloped viruses including human immunodeficiency virus (HIV), hepatitis C virus, dengue virus and influenza virus. This antiviral effect is believed to be due to the indispensability of the calnexin/calreticulin pathway, entry into which is dependent on the trimming of glucoses from N-linked glycans, for the correct folding of viral glycoproteins. Thus cells treated with these drugs are unable to correctly fold the envelope glycoproteins of viruses with the result that the secreted virions have diminished infectivity. A long standing question arising from this hypothesis is how such a mechanism can prove to be damaging to such a wide range of viral glycoproteins yet not show any significant cytotoxicity. This thesis answers that question by demonstrating that, at antiviral concentrations, only a small proportion of viral glycoproteins are misfolded suggesting an amplification effect from protomer oligomerisation and clustering. This thesis also shows how α-glucosidase inhibition results in abnormal disulphide bond formation and isomerisation of the HIV envelope protein, gp120, during folding, as well as faster transit times through the secretory pathway, both potentially explaining the observed misfolding. A specific glycan, N241, is identified as the potential key for gp120/calnexin interaction. α-glucosidase inhibitors have two effects on glycoproteins; inhibition of calnexin mediated folding but also on the structure of the resultant glycan. This thesis uses mannosidase inhibiting iminosugars to examine the comparative significance of each of these to the antiviral effects of iminosugars. This thesis confirms that failure to process glycans beyond glucose trimming can be substantially antiviral in at least one HIV isolate. Finally this thesis looks at the potential for using α-glucosidase inhibiting iminosugars as antivirals against Ebola virus in a guinea pig model. These experiments show that iminosugars are safe, even at very high doses, when given intravenously in animals and that one of them, NB-DNJ, may offer partial protection against Ebola virus, allowing 1/4 guinea pigs to survive a lethal dose of the virus. Although preliminary, this is the first time that a licensed drug has been shown to be antiviral against Ebola virus and shows the potential utility of these drugs as protection against emerging viral infections for which specific therapies are not yet available.